Peningkatan Pemahaman terhadap KUHAP Baru melalui Penyuluhan Hukum tentang Persiapan Persidangan bagi Warga Binaan Rumah Tahanan Kelas I Depok - Suwarsit; Heru Sugiyono; Yuliana Yuli Wahyuningsih; Citraresmi Widoretno Putri; Aisyah Nikita Permata Putri (PT. Adriani Mandiri Publisher, 2026)
The enactment of Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code (KUHAP) has introduced various changes to Indonesia’s criminal justice system, particularly regarding the strengthening of the rights of suspects and defendants, the guilty plea mechanism, the implementation of restorative justice, and the regulation of ordinary and summary trial procedures. These changes require greater procedural legal literacy, particularly among correctional inmates, to enable them to understand their legal status, rights, and the procedural options available throughout the criminal justice process. This community service activity aimed to improve the understanding of correctional inmates at the Class I Depok State Detention Center regarding preparations for criminal trial proceedings under the new Criminal Procedure Code. Particular emphasis was placed on the rights of suspects and defendants, the stages of criminal proceedings, access to legal assistance, and available case-resolution mechanisms. The activity involved 36 correctional inmates and was conducted through interactive lectures and question-and-answer discussions supported by instructional materials. The topics covered included the right to legal representation by an advocate and the possibility of resolving cases through restorative justice. The results demonstrated that the participants gained a better understanding of the stages of criminal trial proceedings, their procedural rights, and the importance of obtaining legal assistance when facing criminal proceedings. The interactive discussions also indicated an improvement in the participants’ ability to identify legal issues related to their position as individuals involved in the criminal justice process.